Symposium 7: Developing a Design Methodology for Web 2.0 Mediated Learning - Buus, Lillian; Georgsen, Marianne; Ryberg, Thomas; Glud, Louise Nørgaard; Davidsen, Jacob (Proceedings of the International Conference on Networked Learning, 2010)
In this paper we discuss the notion of a learning methodology and situate this within the wider frame of learning design or “Designing for Learning”. We discuss existing work within this broad area by trying to categorize different approaches and interpretations and we present our development of particular ‘mediating design artefacts’. We discuss what can be viewed as a lack of attention paid to integrating the preferred teaching styles and learning philosophies of practitioners into design tools, and present a particular method for learning design; the COllaborative E-learning Design method (CoEd). We describe how this method has been adopted as part of a learning methodology building on concepts and models presented in the other symposium papers, in particular those of active, problem based learning and web 2.0-technologies. The challenge of designing on the basis of an explicit learning philosophy, and still trying to develop a design method or tool with a certain general applicability is discussed at the end of the paper. Experiences from a recent design workshop are described and discussed, with a focus on what specific steps have been taken in order to apply the method successfully within the EAtrain2 project as a way of enabling teachers and practitioners to collaboratively design courses. As part of the collaborative e-learning design (CoED) method and the broader learning methodology the authors held a workshop for the project partners in the EATrain2 project, and the results and inputs from this workshop will be briefly discussed in this paper and in the symposium presentation.